Economic and Political Perspectives on Integration in the Baltic Sea Region - Andreas P. Cornett (European Regional Science Association (ERSA), 2003)
The purpose of this paper is to address the influence of the changes in the European economic landscape in the aftermath of the break up of the iron curtain and the new dynamics of the process of European integration in the since 1989. The main focus is on the interaction between political and economic aspects of transition and reintegration in the Baltic Sea Region (BSR). In the first section a concept of spatial integration is sketched based on political and economic concepts of integration. The second part provides a brief record of political and economic integration and reintegration in the Baltic Sea Region. The central hypothesis is that the region has embarked on a path toward a coherent economic and political region with regard to political and economic affiliation. We have seen a consolidation of the old market economies within one trading block, and the former state trade economies will join the EU within two years. The old division of the Nordic countries into two different blocks concerning security policy seems also to diminish. In the same period, the cleavages between East and West with regard to security policy and economic system have disappeared. The paper aims to provide a comprehensive assessment of this process at the end of the first phase of transition at the threshold of the creation of a unified economic space in the Baltic Sea Region. The empirical section will contain information on economic flows as well as an assessment of the institutional changes within the BSR and the emerging new system of production and division of labor in the area. The final section will, based on the concept of spatial integration discuss, whether or not the BSR constitutes a functional region within the European regional system. Keywords: European economic integration - Transition and transformation in the BSR - The BSR in the European regional system - Trade and Production in the BSR
Keywords: 330